Bacteriological Assessment of Ready-to-Eat Bakery Products Sold in Zuru Metropolis, Kebbi State, Nigeria - Galadima, Musa (B R Nahata Smriti Sansthan International Journal of Phramaceutical Sciences & Clinical Research, 2021)
Ready-to-eat foods made from wheat and flour are rich in essential nutrients such as proteins, fats, minerals, and carbohydrates which may increase exponential microbial proliferation in these products when kept under improper storage conditions or through unhygienic handling and as a result cause mild-to-severe illnesses when consumed. This study was conducted to determine the bacteriological value of bakery products sold in Zuru metropolis, in Kebbi state, Nigeria. A total of 20 samples were collected from different bakeries and hawkers and examined using the conventional bacterial isolation, identification, biochemical tests, and enumeration. The total viable bacterial number of the samples demonstrated the highest (12.638 × 107) count in sample (doughnut), while the lowest (1.519 × 107) count was observed in bread factory. The biochemical identification of the isolates revealed the presence of Salmonella species, Escherichia coli, Staphylococcus aureus, Bacillus cereus, and Pseudomonas aeruginosa. The frequency and percentage occurrence of the isolates indicated the highest frequency of 8 and a percentage occurrence of 40% for E. coli, while the lowest frequency of 2 and a percentage occurrence of 10% for S. aureus. This level of bacterial contamination may be attributed to poor handling, preparation, and/or marketing of the baked foods. Moreover, as such safe hygienic practices are recommended during the production and service of these foods.